Recent Advances in Supported Metal Catalysts and Oxide Catalysts for the Reverse Water-Gas Shift Reaction - Chen, Xiaodong; Chen, Ya; Song, Chunyu; Ji, Peiyi; Wang, Nannan; Wang, Wenlong; Cui, Lifeng (Frontiers in Chemistry, 2020)
The reverse water-gas shift reaction (RWGSR), a crucial stage in the conversion of abundant CO2 into chemicals or hydrocarbon fuels, has attracted extensive attention as a renewable system to synthesize fuels by non-traditional routes. There have been persistent efforts to synthesize catalysts for industrial applications, with attention given to the catalytic activity, CO selectivity, and thermal stability. In this review, we describe the thermodynamics, kinetics and atomic-level mechanisms of the RWGSR in relation to efficient RWGSR catalysts consisting of supported catalysts and oxide catalysts. In addition, we rationally classify, summarize and analyse the effects of physicochemical properties, such as the morphologies, compositions, promoting abilities, and presence of strong metal-support interactions (SMSI), on the catalytic performance and CO selectivity in the RWGSR over supported catalysts. Regarding oxide catalysts (i.e., pure oxides, spinel, solid solution, and perovskite-type oxides), we emphasize the relationships among their surface structure, oxygen storage capacity (OSC) and catalytic performance in the RWGSR. Furthermore, the ability of perovskite-type oxides to enhance the RWGSR with chemical looping cycles (RWGSR-CL) is systematically illustrated. These systematic introductions shed light on development of catalysts with high performance in RWGSR.